The Influence of Financial Literacy and Risk Perception on Investment Decisions Based on Gender using Multi-Group Analysis Methods - Marlinia Qibthiyah; Widyastuti, Umi; Ulupui, IGKA (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to analyze the influence of financial literacy and risk perception based on gender using a multi-group analysis method on workers consisting of the millennial and Z generations in Indonesia. A questionnaire-based survey will be conducting using purposive sampling technique. In total, 211 responses were collected and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and also Multi-group Analysis (PLS-MGA) to see the differences in the influence of each gender group. This study enriches the theoretical foundations of financial vulnerability through the exploration of moderation mechanism. Based on the data analysis, this study proved that there is a positive impact of financial literacy and risk perception on investment decisions which moderated by gender.